Design, Construction, and Performance Analysis of a Portable Solar Panel for Efficient Smartphone Charging - Tri Joko; Erlina; Doni Pratama (ZETROEM, 2026)
This study aims to design, construct, and analyze the performance and efficiency of a portable solar panel system specifically developed for smartphone battery charging as an environmentally friendly alternative energy solution. With the increasing reliance on portable electronic devices and the urgent need to reduce fossil fuel dependency, a highly mobile and efficient charging system is required for outdoor or off-grid situations. The research utilizes a quantitative experimental method, employing a 20 Watt-Peak monocrystalline solar panel, a 12V 7Ah storage battery, a Solar Charge Controller (SCC) to regulate energy flow safely, and a buck converter to adjust the output voltage for smartphones. The portable system was integrated into a compact suitcase design for high mobility. Performance testing was conducted over seven consecutive days from 08:00 to 16:00, measuring voltage, current, power output, charging time, and overall system efficiency. The results indicate that the solar panel's output power is highly dependent on sunlight intensity, reaching its maximum peak of up to 15.40 W at midday while maintaining a relatively stable voltage range. The system demonstrated the capability to gradually and safely charge a smartphone battery up to 80% capacity. The highest overall system charging efficiency recorded during the testing period was 55.5%. In conclusion, the designed 20 WP portable solar panel system exhibits stable performance and adequate efficiency, making it a highly practical, reliable, and sustainable off-grid power source for charging portable electronic devices.